Eksplorasi Interaksi Sosial Anak Berkebutuhan Khusus dalam Pembelajaran IPA Berbasis Proyek (PJBL) - Fajarwati, Salsabila; Khoirun Nisa; Minsih (Jurnal Pendidikan Modern, 2025)
Social interaction is one of the skills of human life with others. In inclusive learning, social interaction can be found in the project-based learning (PjBL) learning model. This article aims to 1) describe the social interactions of students with special needs in inclusive schools, 2) describe the role of the project-based learning (PJBL) learning model in creating learning interactions of students with special needs in inclusive schools. This type of research is qualitative research with interview and observation data collection techniques. The results of the study obtained 1) social interactions that occur in inclusive elementary schools still require special attention, and need adjustment and foster a culture of mutual respect in schools, 2) project-based learning provides a role in creating social interactions of regular and special needs students where they help each other in project work. Students with special needs who previously rarely interacted are encouraged to join their friends.